First record of the genus Vailimia Kammerer, 2006 from India, with the description of two new species (Araneae: Salticidae: Plexippina) - Basumatary, Paris; Caleb, John T.d.; Das, Sangeeta; Jangid, Ashish Kumar; Kalita, Jatin; Brahma, Dulur (Zootaxa, 2020)
The genus Vailimia Kammerer, 2006 is recorded for the first time from India. Two new species, Vailimia ajmerensis Caleb & Jangid sp. nov. (♂), and V. jharbari Basumatary, Caleb & Das sp. nov. (♂♀), are described and illustrated in detail. Presently, the genus is known only by the males, which means that the female of V. jharbari described herein is the first female known in the genus.